2023
DOI: 10.1134/s0006297923030094
|View full text |Cite
|
Sign up to set email alerts
|

Role of BDNF in Neuroplasticity Associated with Alcohol Dependence

Abstract: Chronic alcohol consumption is characterized by disturbances of neuroplasticity. Brain-derived neurotrophic factor (BDNF) is believed to be critically involved in this process. Here we aimed to review actual experimental and clinical data related to BDNF participation in neuroplasticity in the context of alcohol dependence. As has been shown in experiments with rodents, alcohol consumption is accompanied by the brain region-specific changes of BDNF expression and by structural and behavioral impairments. BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…On the other hand, in an operant ethanol self-administration paradigm, subchronic administration of DHF enhanced reinstatement in rats [ 20 ]. These and other findings [ 8 , 21 ] suggest that the role of BDNF in AUD may vary between different aspects of the disorder.…”
Section: Introductionsupporting
confidence: 65%
“…On the other hand, in an operant ethanol self-administration paradigm, subchronic administration of DHF enhanced reinstatement in rats [ 20 ]. These and other findings [ 8 , 21 ] suggest that the role of BDNF in AUD may vary between different aspects of the disorder.…”
Section: Introductionsupporting
confidence: 65%
“…Similarly, immune factors that are recruited during alcohol dependence (e.g., TNF-α, IL-6, BDNF, etc.) have been shown to modulate inhibitory and excitatory synaptic transmission via the modulation of neurotransmitter release and receptors ( Roberts et al, 2019 ; Li et al, 2022 ; Peregud et al, 2023 ; Coleman and Crews, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the GDNF serum levels were found to be significantly decreased in patients with alcohol dependence, while a decrease in the BDNF levels is associated with alcohol withdrawal [111,112]. In another study, it was shown that alcohol-related changes in the BDNF levels are related to the macrostructure and the processes of polymorphism and neuroplasticity in the brain, whereas increases in the levels of this neurotrophic factor are correlated with cognitive impairment, anxiety, and depression [113][114][115]. Neurotrophic factors regulate the corelease of neurotransmitters and dictate the cholinergic and adrenergic properties of the neuronal cells.…”
Section: Influence Of Alcohol On Neurotrophic Factors In the First Brainmentioning
confidence: 61%